The Effect of E-Service Quality, Security, and Promotion on Customer Satisfaction of E-Commerce Shopee - Prami Dewi, I Gusti Ayu Wilya Susmitha; Surya Astitiani, Ni Luh Putu; Widnyani, Ni Made (Westscience Press, 2024)
The rapid advancement of information technology has led to the convergence of telecommunications and computer technologies. This shift has also influenced consumer behavior, with a growing number of individuals becoming more accustomed to online shopping, resulting in an increasing number of e-commerce users. Shopee, the leading e-commerce platform in Indonesia, has the highest number of website visits, positioning it as the top e-commerce site in the country. The purpose of this study is to analyze how e-service quality, security, and promotions influence e-customer satisfaction with Shopee among Generation Z in Denpasar. The study employs a descriptive quantitative research method with a sample size of 100 respondents. The t-test results for e-service quality reveal a t-value of 5.930, which is greater than the critical value of 1.984, indicating a significant positive effect of e-service quality on customer satisfaction. Conversely, the security variable demonstrates a negative impact on customer satisfaction, with a t-value of -2.842, which is less than the critical value of 1.984. The promotion variable exhibits a positive effect on customer satisfaction, with a t-value of 4.916, exceeding the critical value of 1.984. Furthermore, the overall hypothesis is supported as the calculated F-value of 62.474 exceeds the F-table value of 2.70, indicating that e-service quality (X1), security (X2), and promotions (X3) collectively influence customer satisfaction (Y).